EVALUASI KEPUASAN PENGGUNA TERHADAP APLIKASI AUDIO BOOKS - Raditya Maulana Anuraga; Ema Utami; Hanif Al Fatta (Universitas Muhammadiyah Ponorogo, 2017)
Listeno is the first application audio books in Indonesia so that the users can get the book in audio form like listen to music, Listeno have problems in a feature request Listeno offline mode that have not been released, a security problem mp3 files that must be considered, and the target Listeno not yet reached 100,000 active users. This research has the objective to evaluate user satisfaction to Audio Books with research method approach, Nielsen. The analysis in this study using Importance Performance Analysis (IPA) is combined with the index of User Satisfaction (IKP) based on the indicators used are: Benefit (Usefulness), Utility (Utility), Usability (Usability), easy to understand (Learnability), Efficient (efficiency) , Easy to remember (Memorability), Error (Error), and satisfaction (satisfaction). The results showed Applications User Satisfaction Audio books are quite satisfied with the results of the calculation IKP 69.58%..